Pengaruh Penggunaan Smartphone Terhadap Perubahan Perilaku Siswa (Studi Kasus Siswa Sekolah Menengah Atas Negeri 5 Palembang) - Muhammad Miftah Farid; Hafid Furqon (Jurnal Studi Sosial dan Politik, 2018)
The era of Technology and Information which is now completely practical and fast certainly makes many people want to try to participate in it. Smartphones are smart phones that have evolved to this day become a tool that can be used by many people to not only communicate, but also to entertain themselves, to get information, learn to work and online selling. Smartphones are getting more and more years, so they are growing rapidly, especially to the millennial generation and the current generation Z is feared to be able to influence changes in their daily behavior. Smartphones that become daily needs for teenagers will certainly be viewed from various sides, whether a big positive and negative affect on the behavior that they apply every day. The number of smartphone users from existing data shows the amount of enthusiasm of teenagers to access the internet through smartphones. This research was made with the title "Effect of Smartphone Use on Changes in Student Behavior (Case Study of Senior High School Number 5 Palembang Students). Has a formulation of the problem of how the influence of smartphone usage on student behavior changes in senior high school 5 Palembang. The purpose of this study was to determine the effect of the use of smartphones on the change in student behavior in state high school number 5 Palembang. This research uses quantitative methods. The source of the data used is obtained through questionnaires, observations and interviews. And using data analysis techniques, namely descriptive analysis techniques and inferential analysis techniques. The theoretical framework used is the theory of Social Penetration. Based on the analysis of the data used and the simple Linear test, it was concluded that the use of smartphones has a very big influence on the changes in student behavior in senior high school number 5 Palembang. In this case it was also found that smartphone usage had a positive effect on changes in student behavior in senior high school number 5 Palembang.